Identification of the RHD novel allele c. 801+2T>G and study of its effect on RhD phenotype in vitro - JIA Shuangshuang; WEN Jizhi; WEI Ling; ZHANG Runqing; LUO Guangping; JI Yanli (Zhongguo shuxue zazhi)
[Objective] To further identify the RhD phenotype and RHD genotype in the individual who have RhD negative phenotype in the primary screening, and to analyze the effect of c. 801+2T>G mutation on RhD phenotype by minigene splicing assay. [Methods] The serologic test was performed for RhD phenotype identification and absorption-elution test was performed by using monoclonal anti-D. Sanger sequencing was used to analyze the sequence of RHD genes and the newly identified splicing site mutations of RHD genes were used to construct pSplicePOLR2G micro gene expression plasmids. By using an in vitro micro gene splicing system, the mRNA splicing results were detected and analyzed using agarose and capillary electrophoresis to predict their impact on RhD phenotype. [Results] The serological test results showed that the patient's blood type was RhD-negative, but the anti-D absorption-elution test was positive, indicating a Del phenotype. The rare genotype RHD*(1227A/801+2G) was identified in this individual. The c. 801+2T>G was a novel mutation at 5'-splice site of intron 5. The minigene splicing assay showed that c. 801+2T>G resulted in a complete skipping of RHD exon 5 in the mature transcript, forming a transcript without exon 5. [Conclusion] An individual carrying a novel mutation c. 801+2T>G in the RHD gene was found to exhibit a Del phenotype, but also carry the Asian Del allele c. 1227G>A. It was speculated that the c. 801+2T>G mutation caused RhD negative or Del phenotype based on the results of minigene splicing assay in vitro.